Silicon pad detectors for a simple tracking system and multiplicity detectors creation - Bochek, G.L.; Kulibaba, V.I.; Maslov, N.I.; Naumov, S.V.; Starodubtsev, A.F. (Вопросы атомной науки и техники, 2001)
Silicon pad detectors are working at room temperatures, what is very convenient for creation of simple tracking system and multiplicity detectors. Silicon pad detectors are studied to create a compact detecting systems for active beam collimation and for gamma-radiation multiplicity measurements. The registration efficiency and spectral distributions of gamma-radiation and electrons were studied using isotope radiation sources. The silicon pad detectors were designed at NSC "KIPT".